Finite element modeling simulation-assisted design of integrated microfluidic chips for heavy metal ion stripping analysis. (18th September 2017) - Hong, Ying; Zou, Jianhua; Ge, Gang; Xiao, Wanyue; Gao, Ling; Shao, Jinjun; Dong, Xiaochen
Abstract: In this article, a transparent integrated microfluidic device composed of a 3D-printed thin-layer flow cell (3D-PTLFC) and an S-shaped screen-printed electrode (SPE) has been designed and fabricated for heavy metal ion stripping analysis. A finite element modeling (FEM) simulation is employed to optimize the shape of the electrode, the direction of the inlet pipeline, the thin-layer channel height and the sample flow rate to enhance the electron-enrichment efficiency for stripping analysis. The results demonstrate that the S-shaped SPE configuration matches the channel in 3D-PTLFC perfectly for the anodic stripping behavior of the heavy metal ions. Under optimized conditions, a wide linear range of 1–80 µ g l −1 is achieved for Pb 2+ detection with a limit of 0.3 µ g l −1 for the microfluidic device. Thus, the obtained integrated microfluidic device proves to be a promising approach for heavy metal ions stripping analysis with low cost and high performance.